Challenges of the World Trade Organization as a consequence of the eleventh ministerial conference held in Buenos Aires - Zúñiga Schroder, Humberto (2018)
The World Trade Organization is an international body that, to date, has more than 20 years of existence. The last ministerial conference, held in Buenos Aires in December of 2017, has posed some challenges that must be addressed by all its members, not only to strengthen the multilateral trading system, but also to achieve a successful outcome of the Doha Round, which started in 2001. The purpose of this paper is to analyze the most important ministerial decisions reached in Buenos Aires, and to give a brief insight into the nature of the problems that were addressed in such decisions.